Manipulating spatial distance in virtual reality: Effects on treadmill walking performance in patients with intermittent claudication. (February 2018) - Cuperus, Anne A.; Keizer, Anouk; Evers, Andrea W.M.; van den Houten, Marijn M.L.; Teijink, Joep A.W.; van der Ham, Ineke J.M.
Abstract: Research indicates that the manipulation of spatial distance between objects in a previously observed environment may go unnoticed when the categorical information of these objects, such as their order, matches that of memory for the environment. Using a repeated measures design, we investigated whether manipulations of spatial distance in virtual reality (VR) can influence treadmill exercise performance (i.e., walking distance) in patients with intermittent claudication; a cramping pain or discomfort in the legs, which occurs during exercise. Participants (N = 19) carried out four treadmill exercise sessions; one without VR and three with a VR environment to move through while walking. They were instructed to walk until the pain forced them to stop. All VR sessions contained the same environment, but in the second and third session it was 'stretched' and 'compressed'. Walking distance was not influenced by the mere addition of VR. However, both VR manipulations led to greater walking distance than the VR baseline session and participants walked furthest when presented with the stretched environment. The results indicate that the manipulation of spatial distance in VR can be of clinical relevance; a finding that may be applied in the development of future medical applications. Highlights: Patients with intermittent claudication walked with and without virtual reality. Walking distance (main outcome measure) was not influenced by adding virtual reality. Stretching and compressing the virtual environment led to increased walking distance. Participants walked furthest when presented with the stretched virtual environment. The results indicate that manipulating spatial distance can be of clinical relevance.